An exploration of reasons behind service delivery protests in South Africa: A case of Bolobedu South at the Greater Tzaneen Municipality - Mamokhere, J. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
This paper aimed at exploring the underlying reasons behind municipal service delivery protests at Greater Tzaneen Local Municipality. South African municipalities also form part of concerned public entities in terms of service delivery backlogs and protests behind service delivery. Over the past few years, South Africa has experienced a large number of protests against poor and insufficient service delivery across most municipalities in various provinces. Therefore, an increase in service delivery protests in South African municipalities, as regularly seen in various media platforms such as newspapers, television and social media makes it necessary for policy-makers, government practitioners and scholars to understand the underlying factors behind service delivery protests. This paper also intended to explore if whether community members protest due to poor or sufficient service delivery. It is quite evident that some people take advantage of the protests to their best interests rather than protesting for better service delivery. To accomplish the aim of this paper, a desktop research approach was applied to validated the argument and to uncover the underlying factors of service delivery protests. From the literature perspective, it is discovered that unemployment, poverty and lack of access to information, political instability, corruption, nepotism and lack of public participatory are underlying factors behind service delivery protests. Despite some of the success of the post-apartheid South African government, the country still faces some serious challenges of high unemployment, poverty, inequality and political instability. These are some of the key factors which culminate in citizens on streets protesting or expressing their dissatisfaction over the problem of poor service delivery.
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Dissatisfaction; Poverty; Protests; Service delivery; Unemployment; Basic needs; Local government --South Africa